A low-temperature active and selective bimetallic Cu-In catalysts for hydrogenation of methyl 3-hydroxypropionate to 1,3-propanediol - Chuanming Zhang; Jincan Kang; Wen Dai; Yanbo Peng; Yiling Zhao; Xiaoang Yang; Bingni Liu; Hongping Zhu (Heliyon)
The pathway for producing 1,3-propanediol (1,3-PDO) from methyl 3-hydroxypropionate (3-HPM) has great application potential. However, the reaction is sensitive to temperature and results in reduced product selectivity at high temperatures. This study explores the use of low-temperature active Cu−In bimetallic catalysts for the 3-HPM reaction. The Cu-1In/SiO2 catalyst exhibits superior catalytic performance with a 91.5 % yield of 1,3-PDO, surpassing that of the Cu/SiO2 catalyst by 264 % under identical conditions. Multiple characterization methods reveal the textural and physiochemical properties of the catalysts. The excellent catalytic performance of Cu-1In/SiO2 can be attributed to the introduction of CuIn alloy and highly dispersed In2O3. The interaction between copper and Indium species on the catalyst surface facilitates the dispersion of Cu species, while simultaneously highly dispersed In2O3 introducing new adsorption sites for reactants, thereby greatly improving its catalytic performance.